Mechanisms involved in maintaining the corpus luteum during the first two months of pregnancy - Drum, Jéssica Nora (2019)
The progesterone (P4) produced by the corpus luteum (CL) is essential for maintenance of pregnancy. On the other hand, the interferon tau (IFNT) produced by the embryo during elongation process, besides being the primary signal for recognition, also is responsible for maintenance of the CL during early pregnancy. The presence of oxytocin receptors (OXTR) in endometrium during expected time of luteolysis is determinant for trigger the uterine release of prostaglandin F2∝ (PGF), which is in charge of CL regression. The IFNT avoid the luteolysis by suppressing the OXTR appearance. However, during second month, accessory CLs are able to regress, indicating that the PGF release occurs with the advancing of the pregnancy and the mechanisms that initiated luteolysis are recovered. Therefore, failures in maintenance of the CL can cause luteolysis and pregnancy loss during this period of 30 to 60 days, which is one of the most important problems in reproductive efficiency in cattle, specially when in vitro produced (IVP) embryos are transferred. Two experiments were designed to study this factors, focused on point when uterus recover its PGF release during pregnancy and to identify possible differences between those mechanisms on pregnancies from IVP or artificial insemination (AI) embryos. The first study evaluated circulating PGF metabolite (PGFM) after an oxytocin challenge throughout first two months of pregnancy in lactating Holstein cows. Treatment with oxytocin did not affected PGFM concentration in d11 pregnant (P) and non-pregnant (NP), on d18 had a little increase in P cows, while increased 2-fold in NP cows. Oxytocin-induced PGFM in P cows on day 25 was greater than d18 P, however was lower than P cows on d53 and d60. Days 32, 39 and 46 of pregnancy had intermediate response. The second study evaluated the oxytocin-induced PGFM in Nelore cows pregnant from AI or IVP embryos on days 17 and 31, and its association with factors that can impact in success of the pregnancy, such as P4 levels, conceptus length on d18 and size of the embryo on d32. Also, OXTR and interferon-stimulated gene 15 (ISG15) gene expression were evaluated and located in uterine endometrium. Embryo size on d32 and P4 on d31, were higher in AI than IVP. Cows from IVP on d17 presented lower oxytocin-induced PGFM than AI in the same day, however, d31 for both groups had higher PGF release after oxytocin. On d31 there was similar PGFM increase in synchronized non-inseminated group (NI). The OXTR are highly suppressed on pregnant cows on d18, especially in IVP group, but were high expressed in NI cows and on d32 for both groups, AI being higher than IVP at this day. The ISG15 had irrelevant expression on NI and d32 groups, while had extremely high expression in d18 pregnant cows for both groups. Concluding, the CL in early pregnancy is maintained by PGF release suppression, while during second month there is oxytocin-induced PGF release, suggesting that other mechanisms are responsible for maintaining CL after d25. In addition, these results demonstrate there are signaling differences between IVP and AI pregnancies, impacting the molecular and endocrine environment that influences PGF release during these time points.